Mourning and professional training: before and after COVID (Research, Society and Development, 2022)
In the world scenario, studies and discussions about mourning have become pertinent when it comes to losses and feelings of grief. To health professionals, especially those who work in hospitals, it is inevitable in their practice not to come across death and mourning of patients and loved ones. Many trainings prepare future professionals for death, but not to deal with its repercussion itself. In this sense, the question arises about the professional in training who is going through personal mourning when facing the death of a family member and who also attends to bereaved patients. Based on this assumption, this research aimed to understand grief and education for life and death in health professionals before, during and after COVID-19. A qualitative systematic review research was conducted with the main theoretical findings of the national and international literature about studies and applications involving grieving process and death with academics and health professionals. More specifically, if there are courses and regions that concentrate more research on the subject. Among the results of the analysis, 27 articles were found that presented mourning as a theme and that approached education for death. Given the results, it was possible to understand the need for preparation of professionals to deal with death beginning in undergraduate and continuing education, as well as support strategies for grief.